Sprunghöhenerfassung mittels des Kinexon© Tracking-Systems - eine Pilotstudie - Javanmardi, S.; Baumgart, C.; Hoppe, M. W.; Freiwald, J. (Leipziger Sportwissenschaftliche Beiträge, 2022)
Summary: This pilot study aimed to compare a Kinexon© tracking system with integrated inertial sensor technology (IMU) with established measurement systems in the measurement of maximum jump height during vertical jumps with (SSJ) and without inrun (CMJ). Six athletes (age: 27 ± 2 years) completed ten jumps each, using an IMU, an infrared sensor, and/or force plates (gold standard). The results were evaluated by calculating the Pearson correlation coefficient. The IMU data showed a medium correlation in comparison (CMJ r = 0.62 - 0.8; SSJ r = 0.74). At present, the determination of the maximum jump height must be judged as not sufficiently valid.